Optimizing Silver Nanoparticle Properties: Synergistic Effects of Green Synthesis and Calcination on Crystallinity, Stability, and Bioactivity - Omar, Sleman Yousif; Qader, Ibrahim Nazem; Pekdemir, Sibel Selcuk; Ahmed, Asmaa Sayed; Babakr, Karukh Ali; Razaq, Chawan Hazhar; Omer, Peshang Khdir (Springer, 2026)
Microbial infections are a major healthcare challenge, exacerbated by rising antibiotic resistance. This study aims to synthesize and characterize silver-based nanoparticles (Ag2O and Ag NPs) via conventional and green routes using Corchorus olitorius leaf extract. Structural, optical, and antibacterial properties were analyzed using XRD, FTIR, and UV-Vis spectroscopy. Antibacterial efficacy was evaluated through disc diffusion, MIC, MBC, and biofilm inhibition assays. Statistical analysis was performed using two-way ANOVA to ensure result reliability. The XRD analysis confirmed that S1 (conventional synthesis) consists of cubic Ag2O, while S2 (uncalcined green-synthesized NPs) and S3 (calcined green-synthesized NPs) exhibit cubic metallic Ag. The crystallite size increased from S2 (16.11 nm) to S3 (31.73 nm), with improved crystallinity (S3: 93.58%). SEM images revealed that green-synthesized nanoparticles (S2, S3) were more uniform and well-dispersed compared to S1. TG analysis indicated that calcination effectively removed organic residues, enhancing nanoparticle stability. Antibacterial tests demonstrated strong activity against E. coli and B. cereus, with S1 showing the highest inhibition. MIC and MBC values confirmed the bacteriostatic, and bactericidal nature of all samples, with S2 exhibiting the strongest effect on B. cereus. Antibiofilm results showed that all samples inhibited biofilm formation, particularly at high concentrations. Overall, green synthesis produced highly crystalline Ag NPs with enhanced stability and antimicrobial efficacy. Calcination further improved crystallinity and reduced defects, making S3 the most stable. These findings highlight the potential of Ag NPs for biomedical and environmental applications, with synthesis conditions significantly influencing their structural and biological properties.
Keywords: Green synthesis; Silver oxide nanoparticles; Antibacterial activity; Biofilm inhibition; Corchorus olitorius extract